RELATIONSHIP BETWEEN THE EXISTENCE OF TUNA TO UPPER AND LOWER THERMOCLINE AT FADs IN PELABUHANRATU WATERS, WEST JAVA - Asep Ma'mun; Erfind Nurdin; Asep Priatna; Mahiswara Mahiswara (Indonesian Fisheries Research Journal, 2022)
Knowledge of fish behavior and its relationship to environmental factors is needed to develop fishing gear operating methods to be more effective. Fish targetting is no longer seen from the catch (amount) result. The target fish is no longer seen from the quantity of catch but rather the quality of the catch). This is done to maintain the sustainable use of fish resources. Data collection was conducted from November 24 to December 3, 2015, at Pelabuhanratu. This study aimed to determine the relationship between fish behavior and environmental factors in the upper thermocline (Zona-Up), thermocline and lower thermocline layer (Zona-Un). Observations were carried out at intervals of 6 hours: morning (6:00 - 08:00 WIB), daytime (12:00 - 14:00 WIB), afternoon (18:00 - 20:00 WIB) and evening (00:00 - 02:00 WIB) using echosounder in FADs. Acoustic recording tracks form stars around the FADs. Measurement of environmental factors was achieved using the CTD Sea bird SBE 19 plus V2. The measured environmental parameters were temperature (ºC), salinity (PSU), dissolved oxygen (mg / l), chlorophyll (mg / m3), conductivity (S / m) and seawater density (kg / m3). The results showed that the factors that had a significant relationship between fish abundance and environmental factors in the zone-up were temperature and salinity. In contrast, the key factor in the thermocline and un-zone layers was temperature.